Pengaruh budidaya rumput laut terhadap tingkat kesejahteraan ekonomi masyarakat Desa Wasalabose Kecamatan Kulisusu Kabupaten Buton Utara - Afan; Yusuf, Sarini; Mansyur, Akhmad; Ruslaini; Patiung, Seventry Meliana (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to determine the effect of seaweed cultivation on the level of economic welfare on the community. This research was conducted in Wasalabose Village Kulisusu District Buton Utara Regency in August-September 2022. Location determination is done internationally or purposively. Research data obtained through interviews with respondents. The sample used in this study amounted to 26 respondents or all members of the population using the census method. With data analysis techniques using simple linear regression equations and relative classification tests.The method used in this research is a quantitative descriptive method. The result of the study show that there is a significant effect of seaweed cultivation on the level of economic welfare of the people of Wasalabose Village Kulisusu District Buton Utara Regency. Where every additional 1% seaweed cultivation business will encourage an increase in the economic welfare of the community by 83.1%.